Protein Produced By Lactobacillus Plantarum ATCC 8014 During Stress - Ismatul Nurul Asyikin Ismail; Hairul Shahril Muhamad; Abdul Jalil Abdul Kader; Rosfarizan Mohamad; Hanina Mohd Noor; Salina Mat Radzi; Maryam Mohamed Rehan (World Journal of Science and Technology Research, 2024)
Volume: 1 No: 8 (Page: 174 - 181)